Impact of Online Learning Application and Lecturer Performance on Student Learning Motivation at Faculty of Economics and Business Warmadewa University - Made Setena; Ni Putu Sri Mariyatni; I.A.Sri Meitri (Universitas Warmadewa, 2021)
Motivation in learning has a role to foster a sense of pleasure, passion, and enthusiasm for learning. The lack of learning motivation in distance learning is caused by the process of learning, where students can become less active in conveying their opinions and thoughts, causing a boring learning process. Student learning motivation is also influenced by lecturer performance. The purpose of this study was to examine student learning motivation in online learning at the Faculty of Economics and Business, Warmadewa University. Various methods are applied in distance learning activities, including the google meet application, zoom application, google classroom, youtube, television, and whatsapp social media. Data was collected by distributing questionnaires which were used as research instruments. Sampling was carried out using the saturated sample method or the census method, namely 48 students who took financial management courses as respondents. To test the research instrument, validity and reliability were tested. Classical Assumption Test is used to test the Regression model. Data analysis used multiple linear regression analysis. The results of the analysis show that the application of online learning and lecturer performance has a positive and significant impact simultaneously or partially on student learning motivation at the Faculty of Economics and Business, Warmadewa University. Thus, it can be suggested that to support learning more effectively, it is better to use more varied learning methods and learning support facilities need more attention.